EVALUATING THE QUALITY OF INFOLOKER KAB.KARAWANG WEBSITE USING WEBQUAL 4.0 METHOD - Setiyani, Lila; Tobi, Tobi; Effendy, Femmy (Universitas Lancang Kuning, 2023)
Technology has provided new methods of presenting the information. Information can be easily accessed anywhere and anytime. One of the Regional Governments of Indonesia takes this advantage by creating an information system called InfoLoker Kab. Karawang to make it easier for citizens to find job vacancies. Of this importance, it interests researchers to conduct a study to evaluate the website’s quality based on the dimensions of the WebQual 4.0 method. WebQual is a method for measuring a website's quality based on the end user's point of view. The data source is taken from InfoLoker Kab. Karawang website users through a survey method with a sample of 118 respondents and data analysis using SmartPLS. According to the discussion results, the quality of the InfoLoker Kab. Karawang’s website was good, with ratings of 73.3%, 74.3%, and 62.2% for the dimensions of usability, information quality, and service interaction quality, accordingly. Overall user satisfaction is significantly impacted by the quality of the information and service interactions, but not by usability because usability’s t-value is under 0.96. However, the website's quality can still be improved, particularly in the service interaction dimension, by improving the security of the user's personal information because even though the service interaction quality dimension significantly influences user satisfaction, it has the lowest quality score